Using Remote Sensing to Discover Historic Context of Human‐Environmental Water Resource Dynamics. (14th January 2021) - Brecheisen, Zach; Hamp‐Adams, Nicholas; Tomasek, Abigail; Foster, Erika J.; Filley, Timothy; Soto, Martín Villalta; Reynoso, Lucia Zuniga; de Lima Moraes, Andre; Schulze, Darrell G.
Abstract: Analysis of historic and contemporary high‐resolution imagery can help to fill knowledge gaps in land cover and management history in locations where documentation is non‐existent or records are difficult to access. Historic imagery dating back to the 1960s can be used to structure quantitative investigation and mapping of land use and land cover change across space and time to enhance earth science, policy, and social science research. Imagery can further inform municipal planning and implementation in areas of natural resource allocation, infrastructure, and hazard mitigation. For management and public education, historic imagery can help people to understand environmental processes and the impacts of human activity in the local environment. Here we emphasize the value of high‐resolution historic satellite imagery from the Corona and Keyhole satellite programs to inform environmental research, public education, and environmental management. Within the Region of Arequipa in southern Peru we highlight examples of urban development, agricultural expansion, river channelization, and glacial retreat via comparison of historic and modern satellite imagery. By incorporating these types of historic imagery data in formats accessible to non‐professionals, public engagement as well as research into human‐environmental investigations will be greatly enhanced.